(untitled) (Discussion Papers, 1993)
A sociological survey focussing on ten villages located at various sections of the national border was performed by the HAS Centre for Regional Studies in 1986. This study presents the results of the survey. Through the survey, we attempted to measure the role of borderland situation in the lives of rural inhabitans. A special focus was devoted to the impact of borderland situation in the backwardness of border villages. Our conclusion was that post-1918, with the designation of new national borders, there came a halt in the lives of border towns. A similar phenomenon could be detected in the case of border villages post-1947. However, post-1960, development chances of villages becoming border crossing points have significantly improved in comparison to the surrounding settlements.